Resource considerations for integrated planning of railway traffic and maintenance windows. Issue 1 (June 2018) - Lidén, Tomas; Kalinowski, Thomas; Waterer, Hamish
Abstract: This paper addresses the coordination of railway network maintenance and train traffic. The work extends a previously developed optimization model by considering maintenance resource constraints for crew availability and work time regulations. The aim is to find a long term tactical plan that minimizes the total cost of maintenance and train operations, where train services and train free windows are scheduled such that maintenance can be carried out by a pool of crew resources, which are divided into bases and have limitations on maximum working hours per day and minimum rest time between these working days. A mixed integer linear programming model along with computational experiments are presented which show that these resource considerations can be correctly handled with a moderate increase in model size and solution time. Highlights: Optimal scheduling of both train services and network maintenance windows. Handling of maintenance crew availability and work time regulations. Tight formulation of work sequence constraints. Resource considerations give moderate increase in model size and solution time.